Estimates of Prevalence of Pulmonary Hypertension according to Different International Definitions - Richa Tyagi; Surya Kant; Akshyaya Pradhan; Anupam Wakhlu; Darshan Kumar Bajaj; Jyoti Bajpai (Canadian Respiratory Journal)
Background. Pulmonary hypertension is a dreaded disease associated with considerable morbidity and mortality. The pulmonary hypertension developing due to chronic respiratory disease is a unique subset with symptoms often getting masqueraded by the underlying respiratory condition. The importance of early detection of this complication has been realized worldwide, and recently, the definition of pulmonary hypertension was revised to set the cutoff of mean pulmonary artery pressure (mPAP) at 20 mmHg instead of 25 mmHg at rest. In our study, we have tried to estimate the difference this new definition brings to the prevalence of pulmonary hypertension among interstitial lung disease patients at our centre. Methods. This was a cross-sectional study in which all the patients of ILDs (n = 239) attending the outdoor and indoor Department of Respiratory Medicine, King George’s Medical University, India, for the duration of one year were subjected to transthoracic echocardiography along with measurement of serum pro-B-type natriuretic peptide (BNP) and troponin T values. The data were analyzed using the different definitions, and the prevalence was compared. Result. Incidence of pulmonary hypertension among ILD patients at mPAP cutoff ≥ 25 was 28.9%, while that at value ≥20 mmHg, incidence of pulmonary hypertension increased to 46.0%. An increment of 15–20% in incidence of pulmonary hypertension was observed among different types of ILD when cutoff of mPAP was changed. Conclusion. The new definition helps in a significant increase in the detection of pulmonary hypertension, which certainly helps in earlier detection and better management of patients.